2013
DOI: 10.1071/fp12044
|View full text |Cite
|
Sign up to set email alerts
|

Minirhizotron imaging reveals that nodulation of field-grown soybean is enhanced by free-air CO2 enrichment only when combined with drought stress

Abstract: The rate of N2 fixation by a leguminous plant is a product of the activity of individual nodules and the number of nodules. Initiation of new nodules and N2 fixation per nodule are highly sensitive to environmental conditions. However, the effects of global environmental change on nodulation in the field are largely unknown. It is also unclear whether legumes regulate nodulation in response to environment solely by varying root production or also by varying nodule density per unit of root length. This study ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 49 publications
7
49
0
Order By: Relevance
“…The result showed that, plants under elevated [103] found that nodule numbers were 134% -229% greater in soybeans grown at elevated [CO 2 ] in combination with reduced precipitation, and this response was driven by greater nodule density per unit of root length. Soil moisture also plays vital role in development of nodules since N 2 -fixation is sensitive to soil moisture than the carbon assimilation but the magnitude of the reduction in N 2 fixation depends on the severity of the drought stress as well as the timing of the drought stress relative to plant growth and development [104].…”
Section: Effect Of Elevated Co 2 and Soil Moisture On Root Nodulesmentioning
confidence: 78%
“…The result showed that, plants under elevated [103] found that nodule numbers were 134% -229% greater in soybeans grown at elevated [CO 2 ] in combination with reduced precipitation, and this response was driven by greater nodule density per unit of root length. Soil moisture also plays vital role in development of nodules since N 2 -fixation is sensitive to soil moisture than the carbon assimilation but the magnitude of the reduction in N 2 fixation depends on the severity of the drought stress as well as the timing of the drought stress relative to plant growth and development [104].…”
Section: Effect Of Elevated Co 2 and Soil Moisture On Root Nodulesmentioning
confidence: 78%
“…The papers by Gray et al (2013) and Vandergeer et al (2013) in this volume emphasise the below ground processes and acquisition side of the equation, which are still considerably less explored than above ground plant functions. Plants appear to be able to capitalise on higher atmospheric CO 2 so long as they have access to adequate N, underlining the importance of nitrogen use efficiency in crops (Reich and Hobbie 2012).…”
mentioning
confidence: 99%
“…Legumes such as soybean are putatively better placed to take advantage of increasing [CO 2 ], because of their capability to fix N 2 . The paper by Gray et al (2013) reports direct observations of root nodules in a FACE setup using rhizotrons. Interestingly, elevated [CO 2 ] stimulated nodulation only under drought conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations